RANCANG BANGUN E-COMMERCE BERBASIS WEB UNTUK UMKM BATIK - Nugraha, Syahrul; Hamonangan, Ryan; Dana, Raditya Danar; Tohidi, Edi; Hayati, Umi (LPPM UNIKA Santo Thomas Medan, 2022)
In the sales process carried out by batik craftsmen who are in Trusmi village, namely still selling their batik cloth to the sorum of batik sellers, so that the craftsmen take profits from selling their batik cloth only slightly, because the batik cloth will be resold by the sorum of batik sellers. In terms of application development, the author uses the Software Development Life Cycle (SLDC) model with an approach using the waterfall method, while the stages use the waterfall method, namely communication, planning, modeling, construction, and deployment. Therefore, the author makes an application for selling batik cloth that aims to break the chain of batik cloth sales, so that craftsmen can get greater profits because they directly sell their products to consumers without going through a batik seller sorum. The final result obtained in this study is an application for selling batik cloth which is expected to help batik craftsmen in Trusmi village in selling their batik cloth directly to consumers without having to go through the center of batik sellers. In the sales process carried out by batik craftsmen who are in Trusmi village, namely still selling their batik cloth to the sorum of batik sellers, so that the craftsmen take profits from selling their batik cloth only slightly, because the batik cloth will be resold by the sorum of batik sellers. In terms of application development, the author uses the Software Development Life Cycle (SLDC) model with an approach using the waterfall method, while the stages use the waterfall method, namely communication, planning, modeling, construction, and deployment. Therefore, the author makes an application for selling batik cloth that aims to break the chain of batik cloth sales, so that craftsmen can get greater profits because they directly sell their products to consumers without going through a batik seller sorum. The final result obtained in this study is an application for selling batik cloth which is expected to help batik craftsmen in Trusmi village in selling their batik cloth directly to consumers without having to go through the center of batik sellers.